Preliminary findings of expository discourse in older adults: The impact of cognition, social support, and gender - Kim, Hana; Kintz, Stephen; Wright, Heather (Journal of Language and Aging Research, 2024)
Aims: The purpose of this study was to: 1) examine older adults' ability to deliver coherent discourse in expository discourse elicitation tasks; and 2) explore whether cognitive ability and social behavior activity predict coherent discourse production in healthy older adults, separately by gender. Methods: Study participants included 58 neurologically healthy older adults–male (n\,=\,19) and female (n\,=\,39). For the discourse elicitation task, participants provided their opinion in response to four controversial topics. They also completed executive function measures and social engagement questionnaires. Results: Years of education significantly differed between the two groups; thus, education was used as a covariate. A 2 × 4 mixed analysis of covariance (ANCOVA) was conducted. Main effect differences for gender and topic for discourse coherence were not found. In order to examine the contributions of executive function and social engagement on discourse coherence by gender, multiple regression analysis was conducted. For the male group, social activity and social network were significant predictors of the ability to convey coherent discourse on the healthcare topic. For the female group, only executive function was a significant predictor of the coherent discourse production on the marriage topic. Conclusions: The findings suggest that in the same type of discourse elicitation task, the nature of topic influences performance in elicited expository discourse. Moreover, results indicated that the influence of cognitive ability and social engagement on discourse coherence differed between the two gender groups.